2016
DOI: 10.1002/bmc.3678
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacokinetics of and tissue distribution study of physalin B after intravenous administration in rats by liquid chromatography with tandem mass spectrometry

Abstract: A rapid and sensitive liquid chromatography tandem mass spectrometry quantitative analysis method was established for the pharmacokinetics and tissue distribution study of physalin B in rat. Physalin B and physalin H (internal standard, IS) were separated on an Agilent Eclips XDB C8 column. MS detection was performed on a triple quadrupole tandem mass spectrometer in the multiple reaction monitoring mode with a positive eletrospray ionization source. The assay was validated in the concentration ranges of 22.6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…A recent study reported that physalin B has a relative long dwell time with a half-life of 321.2 ± 29.5 min and clearance of 175.4 ± 25.7 ml/min/kg in rats after intravenous injection (19). Although widely distributed in tissues, physalin B penetration was particularly high in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that physalin B has a relative long dwell time with a half-life of 321.2 ± 29.5 min and clearance of 175.4 ± 25.7 ml/min/kg in rats after intravenous injection (19). Although widely distributed in tissues, physalin B penetration was particularly high in the lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Physalin B (purity [? ]98%) were separated and purified in our laboratory; their structures, shown in Figure 1A, were confirmed by comparing the IR, 1H and 13C nuclear magnetic resonance and MS data with reported data (Zheng, Chen, Liu, Liang & Hong, 2016). Calyx Seu Fructus Physalis (3 kg) were extracted with 95% ethanol for three times.…”
Section: Reagentsmentioning
confidence: 61%
“…Physalin B (purity ≥98%) was extracted and purified in our laboratory and the structure, shown in Figure 1a, was confirmed by comparing the IR, 1 H and 13 C NMR, and MS data with reported data (Zheng et al, 2016). Physalis Calyx seu Fructus (3 kg) were extracted three times, with 95% ethanol.…”
Section: Methodsmentioning
confidence: 77%